Fauna and parasitological analysis of infection of wild birds of Pavlodar region with trematodes of two families (Experimental biology, 2020)
The study of the ways of transmission of parasites of various animals in the light of the ongoing ecosystem transformations caused by natural factors (climate change) and human influence is an urgent problem. In connection with the above, it becomes topical to study the features of the existence of parasites and parasitic systems in changing environmental conditions. This article is devoted to the analysis of long-term data on two taxa of representatives of the class Trematoda of the type Plathelminthes on the territory of Pavlodar region of Kazakhstan.The aim of the research is parasitological analysis of data on trematodes of families Prosthogonimidae and Echinostomatidae, identification of features of centers of distribution of helminths.In the above families the indicators of the invasion intensity of birds of the examined species, the abundance index indicators were analyzed for the first time, the features of the above mentioned indicators from the taxonomic location of the host birds in the studied region were determined.Studying of fauna and prevalence of representatives of families Prosthogonimidae and Echinostomatidae of class Trematoda of type Plathelminthes at wild birds allows to judge that in the Pavlodar region there are rather extensive foci of prostogonimosis of birds which in recent years undergoes changes. Echinostomes of wild birds is widespread among waterfowl hunting commercial species of the region. Wild birds provide maintenance of foci of trematodoses.Key words: helminths, trematodes, wild birds, fauna, parasitological analysis.